Cost Effective Energy-Saving System in Parking Spots - Sungheetha, Akey; R, Rajesh Sharma (Journal of Electronics and Informatics, 2020)
Vehicles are becoming an essential product in everyone’s life. Keeping a vehicle in a safe place will improve the life of its engine and other electrical systems. Hence, parking place occupies a major portion while constructing a house, apartment and shopping malls. The lighting system in such places are utilizing more energy and it leads to unnecessary expense on electricity bills. The proposed microcontroller based energy saving system is developed to minimize the utilization of light energy in parking spaces in an efficient manner. The results of the proposed system is compared with the general operation for identifying its efficiency. The proposed method saves the energy up to 46.35% than the existing lighting system.